DIGITAL LIBRARIES: HISTORY AND MODERNITY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines the development of digital libraries from the first attempts at digital storage of information to modern global network resources. The article analyzes the stages of evolution of digital libraries, their role in transforming access to knowledge, as well as current trends, including open archives, digital collections and copyright issues.